Analisis Isi Saluran Youtube Dondy Tan sebagai Media Dakwah - Denny Setiawan; Farida Hariyati; Abdul Khohar (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This study analyzes the dakwah content produced by Dondy Tan in the YouTube videos "Keotentikan Kitab Suci" and "Ngobrol 2 Jam Berujung Syahadat." The background of this research lies in the significant role of social media, particularly YouTube, in disseminating dakwah information through innovative approaches. Dondy Tan, a convert to Islam who shares both knowledge and personal experiences, utilizes this platform to reach a wider audience. The research aims to evaluate the types of content, the methods of message delivery, and their impact on the audience. The analysis results indicate that the content is effective due to the use of intertextual approaches, argumentative communication styles, and strong visual and auditory elements. In conclusion, credibility and persuasive approaches grounded in a deep understanding of Islamic teachings are crucial in creating impactful dakwah content on social media. This research provides insights for dakwah practitioners in optimizing social media to spread religious messages.